Entwicklung von Modellen zur speichergestützten Versorgung mit regenerativen Energien in Inselnetzen - Itschner, Harald (KIT Scientific Publishing, 2022)
The proposed method for the configuration of renewably powered energy supply systems as isolated grids backed by energy storage technology and based on statistical models shows the economic viability of such a system. The energy supply system was configured by implementing cost models using an optimization software. Validation was achieved through comparison with measurements taken from two different existing energy supply areas.